1984
DOI: 10.2527/jas1984.5861337x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Litter Size Effects on Growth and Reproduction in Rats

Abstract: The effects of postnatal litter size on pre- and postweaning growth, daughter's litter size and rebreeding performance of the dam were examined in rats that had undergone 14 generations of selection for rate (LG) or efficiency (LE) of postweaning protein gain followed by relaxed selection, and in a randomly selected control line (C). Data came from generations 23 to 24 (standardized litters) and 25 to 26 (unstandardized litters). Generation 25 dams were remated at weaning for two additional parities. Regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As it has been shown in previous studies (e.g., Azzam, Nielsen, & Dickerson, 1984;Mendl, 1988;Rödel, Prager, et al, 2008) Males were consistently and significantly heavier than females during the whole study period, even on postnatal day 6, when we weighed the animals individually for the first time (b males ¼ .90, p MCMC ¼ .001; R 2 Nagelkerke ¼ .11). However, there were no interactions between sex and litter size (p MCMC > .30), indicating that litter size effects on body mass had a similar negative slope in both sexes.…”
Section: Body Mass Developmentmentioning
confidence: 75%
“…As it has been shown in previous studies (e.g., Azzam, Nielsen, & Dickerson, 1984;Mendl, 1988;Rödel, Prager, et al, 2008) Males were consistently and significantly heavier than females during the whole study period, even on postnatal day 6, when we weighed the animals individually for the first time (b males ¼ .90, p MCMC ¼ .001; R 2 Nagelkerke ¼ .11). However, there were no interactions between sex and litter size (p MCMC > .30), indicating that litter size effects on body mass had a similar negative slope in both sexes.…”
Section: Body Mass Developmentmentioning
confidence: 75%
“…However, non-lethal consequences of this natural competition may induce important differences in an individual's postnatal life. For example, growth rates are favored for subjects with greater access to maternal milk; these individuals may achieve higher reproductive success and longer lives; thus, a small litter size may represent an evolutionary advantage (Azzam et al, 1984;van Engelen et al, 1995;Stockley and Parker, 2002;Rodel et al, 2008;Rodel et al, 2010). Furthermore, it has been demonstrated that spontaneous litter size changes may affect emotionality in adulthood; these changes could not be explained by concomitant changes in maternal care (Dimitsantos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The negative relationship between litter size and average litter BW is in accordance with previous studies. The study evaluated the effect of litter size on average pup weight in rats using regression analysis showed that the relation was negative and increased in magnitude from birth to weaning (3 wk) [31]. The effect persisted into the postweaning period; although a compensatory growth spurt seemed to occur during wk 3 to 5.…”
Section: Discussionmentioning
confidence: 99%